Geothermal exploration using lineament density analysis at Rajabasa Volcano, South Lampung - Dwi Wahyu Hardiyanto; Agung Setianto (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
The research is located around Rajabasa Volcano, South Lampung Regency, Lampung Province, Indonesia. The research areas have unique geological conditions and arrangements. It is part of the caldera body estimated to have centralized geothermal potential. Identification of potential geothermal areas can be made using remote sensings such as lineament density analysis, slope, and land surface temperature with areas of approximately 190 square Kilometers. Manually extraction of lineament density is dominated by the NW-SE direction with an anomaly of only 20 percent. While the lineament density process is automatically controlled in the NE-SW order, it is estimated that the anomaly density is around 80 percent which is suitable for the central, medial, and distal. The shape of the topographic relief has a reasonably high slope starting from 0 to over 55 degrees. The soil surface temperature ranges from 14 to 34 degrees Celsius. The results of the data analysis variables in the research area should be suspected that the geothermal distribution potential of Rajabasa Volcano is estimated to be in the T0 N-NW zone, T1 E zone, and T2 S-SW zone.